Comparative study of harmonic scalpel haemorrhoidectomy versus conventional (milligan and morgan) haemorrhoidectomy - Mala, Tariq Ahmed; Malla, Shahid Amin; Shah, Ajaz Ahmad; Kapoor, Maria; Gupta, Ved Bushan (International Journal of Research in Medical Sciences, 2017)
Background: Haemorrhoids are dilated veins occurring in relation to the anus. There are various treatment modalities for haemorrhoids and among them surgical treatment is considered to be most effective one. Harmonic scalpel hemorrhoidectomy was compared with conventional in terms of symptomatic relief and complications. Methods: The aim of our study was to compare harmonic scalpel haemorrhoidectomy with conventional in terms of various intraoperative and postoperative factors for the treatment of grade III and IV haemorrhoids. Results: In our case study of 25 patients average time taken was 17.68 ± 2.84 minutes, while it was 28.44 ±3.69 minutes in control group. The mean blood loss was 8.96 ± 2.15 ml, 31.72 ± 3.28 ml in the case and control group respectively. Postoperative pain with VAS in case group on the first postoperative day was 5.92 ± 0.72, while it was 8.52 ± 0 in the control group. The dose of analgesia was less in case group. The postoperative wound site soakage was less in case study, early ambulation and return to normal work was faster in case study group. Conclusions: Harmonic scalpel haemorrhoidectomy is a simple, bloodless, safe and effective procedure in terms of blood loss, postoperative pain early return to routine work because of less lateral thermal injury.